The Sociolinguistic Perspective of Hedging in English - Harutyunyan, Kristine; Sargsyan, Anna (Armenian Folia Anglistika, 2019)
Hedging refers to linguistic strategies which qualify categorical commitment, expressing possibility and probability rather than certainty. Hedges express tentativeness and possibility in communication, so their appropriate use in different discourses is vital. The aim of the present paper is to describe and analyze the social factors and social parameters that influence and determine the use of hedging in English speech; particularly we focus on gender, occupation, topic and setting while examining each type of speech. The famous TED talks (usually short, influential and powerful) serve as a primary source of investigation.
Keywords: sociolinguistic perspective; social interaction; hedging; social factors; TED talks